Metamorphic evolution of granulites from Grovnes Peninsula of Larsemann Hills, East Antarctica: Constraints from phase equilibrium modelling and geochronology - Sorcar Nilanjana; Dev J. Amal; Mukherjee Sneha; Joshi Kumar Batuk; Rao B. Padma (Polar Science, 2023)
Petrology, geothermobarometry, and phase equilibrium modelling of garnetiferous felsic gneiss from Grovnes peninsula in the Larsemann Hills of Prydz Bay, East Antarctica provide pristine evidence for the preservation of high-grade metamorphic imprint in the area. The metamorphic evolution of the sample is demonstrated by the development of the assemblage Grt+Bt+Melt+Pl+Sill+Kfs+Qtz+Ilm at peak metamorphic conditions of ∼790 °C and ∼7.5 kbar, which subsequently underwent retrogression and cooling to lower P-T conditions along a clockwise path. Texturally constrained chemical dating of monazites constrain the timing of peak metamorphism and garnet formation at ∼575 Ma, whereas the apatite U–Pb ages constrain cooling ages at ∼518 Ma. The clockwise P˗T˗t trajectory of the studied samples, together with the Ediacaran-Cambrian metamorphic/cooling ages demonstrate the long-lived nature of metamorphism in Prydz Bay, which is ascribed to collisional tectonism prevalent during the final stages of the assembly of East Gondwana supercontinent. Similar results from adjacent continental fragments including Sri Lanka, Eastern Ghats Belt, Madagascar, and South India suggest their coeval metamorphic evolution during the East African orogeny. journal article